2005
DOI: 10.2116/analsci.21.61
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enantioseparation of 1-Aminoindan by Microchip Electrophoresis with Linear-Imaging UV Detection

Abstract: Chiral separations of 1-aminoindan (AI) by cyclodextrin electrokinetic chromatography (CDEKC) were investigated on microfluidic quartz chips. By using a microchip electrophoresis (MCE) instrument equipped with a linear-imaging UV detector, the separation process of the enantiomeric compounds was observed. When sulfated β-cyclodextrin was employed as a chiral selector, the baseline separation of AI could be achieved within 1 min with a high repeatability. The relative standard deviation of the migration time wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…A variety of channel dimensions have been used; however, the length of the detection area is set to 25 mm by the instrument configuration. The instrument was utilized in testing the applicability of transforming affinity CE (ACE) techniques to microchip format [50], in the rapid separation of antimicrobial metabolites with high efficiency [51], and in chiral separations of pharmaceuticals by CD EKC [52,53]. The same system was employed in developing a method to test for nitrogen monoxide metabolites in biological fluids [54], along with a single-step quantitation of DNA [55], and chip gel electrophoresis method for high-sensitivity DNA detection [56], as well as a monosaccharide derivative separation [57].…”
Section: Absorbance Detectionmentioning
confidence: 99%
“…A variety of channel dimensions have been used; however, the length of the detection area is set to 25 mm by the instrument configuration. The instrument was utilized in testing the applicability of transforming affinity CE (ACE) techniques to microchip format [50], in the rapid separation of antimicrobial metabolites with high efficiency [51], and in chiral separations of pharmaceuticals by CD EKC [52,53]. The same system was employed in developing a method to test for nitrogen monoxide metabolites in biological fluids [54], along with a single-step quantitation of DNA [55], and chip gel electrophoresis method for high-sensitivity DNA detection [56], as well as a monosaccharide derivative separation [57].…”
Section: Absorbance Detectionmentioning
confidence: 99%
“…Prior to separation, 7 mL of the protein sample was introduced into the reservoir S and a platinum electrode was inserted into each reservoir to provide electrical contact. To introduce the sample solution into the separation channel, the pinched injection technique [30,31] was employed as shown in Fig. 1.…”
Section: Mce Analysis Of Proteinsmentioning
confidence: 99%
“…22 The linear-imaging UV detector allows for the MCE analysis of various compounds without any derivatization. 21,[23][24][25][26][27][28][29][30][31] Consequently, a UV detection scheme eliminates the labeling of sample proteins. Recently, Vlčková et al reported on the application of MCE-2010 to the MCIEF analysis of proteins on a conventional cross-channel chip.…”
Section: Introductionmentioning
confidence: 99%